2020
DOI: 10.1017/s1751731120000841
|View full text |Cite
|
Sign up to set email alerts
|

Review: Long non-coding RNA in livestock

Abstract: Less than 2% of mammalian genomes code for proteins, but ‘the majority of its bases can be found in primary transcripts’ – a phenomenon termed the pervasive transcription, which was first reported in 2007. Even though most of the transcripts do not code for proteins, they play a variety of biological functions, with regulation of gene expression appearing as the most common one. Those transcripts are divided into two groups based on their length: small non-coding RNAs, which are maximally 200 bp long, and long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 117 publications
0
30
0
Order By: Relevance
“…The growing number of next-generation sequencing data and the development of computational biology have brought the regulatory role of lncRNA in biological processes to light, which may offer a deeper understanding of the phenotypic variation of complex traits in farm animals [2,52]. In this study, we used transcriptomic data from 18 Nellore bulls, to identify lncRNA expressed in five tissues (hypothalamus, pituitary gland, adrenal gland, muscle and liver) of indicine cattle.…”
Section: Discussionmentioning
confidence: 99%
“…The growing number of next-generation sequencing data and the development of computational biology have brought the regulatory role of lncRNA in biological processes to light, which may offer a deeper understanding of the phenotypic variation of complex traits in farm animals [2,52]. In this study, we used transcriptomic data from 18 Nellore bulls, to identify lncRNA expressed in five tissues (hypothalamus, pituitary gland, adrenal gland, muscle and liver) of indicine cattle.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA is an important member of the group of ncRNAs and plays a critical role in muscle development through the regulation of transcriptional and post-transcriptional gene expression. Previous studies have identified numerous lncRNAs in livestock (such as pig, cattle, and chicken) and have demonstrated that they play key roles in specific developmental stages for different tissues (such as liver, muscle, and adipose tissue) ( Muret et al, 2017 ; Kern et al, 2018 ; Kosinska-Selbi et al, 2020 ). In recent years, several studies have been performed on lncRNA identification and pathway regulation in chicken skeletal muscle development ( Li et al, 2012 , 2017 ; Ren et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The growing number of next-generation sequencing data and the development of computational biology have brought the regulatory role of lncRNA in biological processes to light, which may offer a deeper understanding of the phenotypic variation of complex traits in farm animals [2,52]. In this study, we used transcriptomic data from 18 Nellore bulls, to identify lncRNA expressed in five tissues (hypothalamus, pituitary, adrenal gland, muscle and liver) of indicine cattle.…”
Section: Discussionmentioning
confidence: 99%